2021
DOI: 10.1177/08901171211052279
|View full text |Cite
|
Sign up to set email alerts
|

Process Evaluation in Health Communication Media Campaigns: A Systematic Review

Abstract: Objective. The objective is to examine the scope of health communication media campaign process evaluation methods, findings, and dissemination practices. Data Source. A systematic review of peer-reviewed literature was conducted using database searches. Study Inclusion and Exclusion Criteria. Published studies on process and implementation evaluation of health campaigns with a media component were included. Exclusion criteria included not health, non-empirical, no media campaign, or a focus on other evaluatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 78 publications
(390 reference statements)
1
5
0
Order By: Relevance
“…In the case study of Cordaid’s global health advocacy program, PPE was found to help advocates to better understand the barriers and facilitators of their implementation processes and adjust their strategies accordingly. These findings are in line with process evaluations in other contexts (Getachew-Smith et al, 2022), with PPE being able to adapt to fit the unique needs of an advocacy team. This was enhanced by the stakeholder involvement in the study, which motivated advocates to reflect on their role, work, and knowledge as an individual and as a team, which according to a study by Law et al (2016) is crucial for health advocates to grow in their role.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…In the case study of Cordaid’s global health advocacy program, PPE was found to help advocates to better understand the barriers and facilitators of their implementation processes and adjust their strategies accordingly. These findings are in line with process evaluations in other contexts (Getachew-Smith et al, 2022), with PPE being able to adapt to fit the unique needs of an advocacy team. This was enhanced by the stakeholder involvement in the study, which motivated advocates to reflect on their role, work, and knowledge as an individual and as a team, which according to a study by Law et al (2016) is crucial for health advocates to grow in their role.…”
Section: Discussionsupporting
confidence: 85%
“…In addition, the workshop gathered input on a framework to guide the PPE. The evaluator created a "base framework" using the process evaluation framework (described by Getachew- Smith et al, 2022) and the personal narratives framework (described by Cornwall and Aghajanian, 2017). This framework consists of five key concepts from process evaluation theory: Aims focus on the goals and strategy of the advocacy set before the implementation of the tool or activity and what the expectations were of those involved.…”
Section: Phase Ii: Prioritizing (March 2022)mentioning
confidence: 99%
See 3 more Smart Citations